2014
DOI: 10.1111/jgh.12666
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adiposity trajectories and risk of nonalcoholic fatty liver disease in adolescents

Abstract: Background and Aim Nonalcoholic fatty liver disease (NAFLD) and its metabolic risk factors are recognized during childhood and adolescence. Identification of adolescents at risk of NAFLD from childhood anthropometry may expose opportunities to influence the hepatic and metabolic destinies of individuals. We sought associations between NAFLD diagnosed during adolescence and earlier life trajectories of anthropometry, in a population‐based cohort of predominantly Caucasian adolescents. Methods Assessment for NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 40 publications
1
50
1
Order By: Relevance
“…Among 1170 individuals who underwent ultrasound at age 17, NAFLD was found in 13% and was more common in girls than boys (16% vs 10%); however, this was related to more female individuals being centrally obese . Children with excess weight at age 3 were more likely to have NAFLD in teenage years …”
Section: Prevalence Of Non‐alcoholic Fatty Liver Disease In Australiamentioning
confidence: 99%
“…Among 1170 individuals who underwent ultrasound at age 17, NAFLD was found in 13% and was more common in girls than boys (16% vs 10%); however, this was related to more female individuals being centrally obese . Children with excess weight at age 3 were more likely to have NAFLD in teenage years …”
Section: Prevalence Of Non‐alcoholic Fatty Liver Disease In Australiamentioning
confidence: 99%
“…Furthermore, 4%‐6% of all youth in the United States have severe obesity and gain weight faster than any other subgroup . The importance of these facts is highlighted by studies that demonstrated that obese adolescents are more likely to develop severe obesity by the time they reach their early thirties; childhood adiposity is associated with NAFLD in adolescence; and weight gain in childhood correlates with the entire histological and clinical spectrum of adult NAFLD regardless of initial or attained BMI . A recent large cohort study demonstrated that overweight adolescents (aged 18‐20 years) have an increased risk of severe liver disease (hazard ratio, 1.64; 95% confidence interval [CI], 1.16‐2.32; P = 0.006) compared to those with normal BMI after a follow‐up of 39 years .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Increasing maternal body mass index (BMI) has also been associated with increased neonatal liver fat deposition (10). Long-term human studies are, however, less consistent with birth weight positively associated with adverse liver function or a diagnosis of NAFLD at age 17 years in some (11) but not all studies (12). …”
mentioning
confidence: 99%